Association of dietary macronutrient intake with adiposity during childhood according to sex: Findings from the generation XXI birth cohort - Marinho, AR (2022)
Background/Objectives Few studies have assessed the independent and longitudinal effects of each macronutrient intake on adiposity throughout childhood. We aimed to prospectively assess the independent associations between each macronutrient intake at 4, 7, and 10 years (protein, carbohydrates, fat, and fibre) and each measure of adiposity from 7 to 10 years of age by sex. Methods Data from the population-based birth cohort Generation XXI was used (n = 3999). At 4, 7, and 10 years old, dietary, anthropometric and sociodemographic data were collected. The dietary intake of the children was evaluated by a validated food frequency questionnaire. Age- and sex-specific body mass index z-scores (zBMI), percentage of body fat (%FM) from bio-impedance, and waist-to-hip ratio (Whr) were used as measures of adiposity. Path analysis tested the independent associations between each macronutrient intake (protein, carbohydrates, fat, and fibre) and each measure of adiposity from 7 to 10 years of age. Results In fully adjusted models, an increase in energy from fibre intake at the age of 7 was associated with lower zBMI at the same age (beta = -0.073; 95%CI [-0.127,-0.019]) and at 10 years (beta = -0.083; 95%CI [-0.137,-0.029]). Similar results were found for %FM and Whr, and in each sex separately. At the age of 10, an increase in energy from fibre intake was associated with lower %FM and Whr, while an increase in energy from protein was associated with an increase in Whr (beta = 0.061; 95%CI [0.014, 0.107]). Conclusions Our study supports the protective effect of fibre intake on adiposity development during childhood in both sexes.